Health facility-based Active Management of the Third Stage of Labor: findings from a national survey in Tanzania - Mfinanga Godfrey S; Kimaro Godfather D; Ngadaya Esther; Massawe Sirili; Mtandu Rugola; Shayo Elizabeth H; Kahwa Amos; Achola Ominde; Mutungi Alice; Knight Rod; Armbruster Deborah; Sintasath David; et al. (BMC, 2009)
Abstract Background Hemorrhage is the leading cause of obstetric mortality. Studies show that Active Management of Third Stage of Labor (AMTSL) reduces Post Partum Hemorrhage (PPH). This study describes the practice of AMTSL and barriers to its effective use in Tanzania. Methods A nationally-representative sample of 251 facility-based vaginal deliveries was observed for the AMTSL practice. Standard Treatment Guidelines (STG), the Essential Drug List and medical and midwifery school curricula were reviewed. Drug availability and storage conditions were reviewed at the central pharmaceutical storage site and pharmacies in the selected facilities. Interviews were conducted with hospital directors, pharmacists and 106 health care providers in 29 hospitals visited. Data were collected between November 10 and December 15, 2005. Results Correct practice of AMTSL according to the ICM/FIGO definition was observed in 7% of 251 deliveries. When the definition of AMTSL was relaxed to allow administration of the uterotonic drug within three minutes of fetus delivery, the proportion of AMTSL use increased to 17%. The most significant factor contributing to the low rate of AMTSL use was provision of the uterotonic drug after delivery of the placenta. The study also observed potentially-harmful practices in approximately 1/3 of deliveries. Only 9% out of 106 health care providers made correct statements regarding the all three components of AMTSL. The national formulary recommends ergometrine (0.5 mg/IM) or oxytocin (5 IU/IM) on delivery of the anterior shoulder or immediately after the baby is delivered. Most of facilities had satisfactory stores of drugs and supplies. Uterotonic drugs were stored at room temperature in 28% of the facilities. Conclusion The knowledge and practice of AMTSL is very low and STGs are not updated on correct AMTSL practice. The drugs for AMTSL are available and stored at the right conditions in nearly all facilities. All providers used ergometrine for AMTSL instead of oxytocin as recommended by ICM/FIGO. The study also observed harmful practices during delivery. These findings indicate that there is a need for updating the STGs, curricula and training of health providers on AMTSL and monitoring its practice.